The Politics of Pronunciation: An Examination of Accent and Identity in Nigerian English (NigE) Teaching - Ameh Timothy Ojochegbe; Ortaver Tersoo Timothy; Emmanuel Nicodemus (Riviera Publishing, 2024)
This study investigates the intricate relationship between accent, identity, and pedagogy in Nigerian English Language Teaching (ELT). Despite the growing recognition of Nigerian English (NigE) within global frameworks, Received Pronunciation (RP) remains the dominant model in educational settings, often marginalizing local accents. The primary aim of this research is to explore the implications of accent bias on teaching practices and student perceptions. Using a qualitative research design, data were collected through interviews, classroom observations, and document analysis across various secondary schools in Nigeria. The findings reveal significant tensions between the adherence to RP and the acceptance of NigE, with educators often feeling pressured to conform to foreign norms. Students exhibit linguistic insecurity tied to societal biases favoring RP while expressing pride in their local accents. The study concludes by advocating for curriculum reforms recognizing NigE as a legitimate variety, emphasizing intelligibility over accent conformity. Recommendations include revising teacher training programs to promote inclusive pedagogies that validate linguistic diversity. By embracing NigE, educators can empower students to communicate effectively while celebrating their cultural identities, bridging local and global linguistic contexts.